Development of quantum dot-linked immunosorbent assay (QLISA) and ELISA for the detection of sunset yellow in foods and beverages. (15th August 2022) - Xu, Long; Yang, Fanfan; Dias, Alberto C.P.; Zhang, Xiaoying
Graphical abstract: Highlights: A sunset yellow (SY) hapten was synthesized by diazo-reaction. QLISA (LOD: 1.0 ng/mL) and ELISA (LOD: 0.2 ng/mL) were developed for SY analysis. QLISA and ELISA could be used to detect SY in foods and beverages. The two methods showed good agreement in SY detection in spiked and real samples. Abstract: Sunset yellow (SY) is widely used as food colorant. Excess and illegal use of SY could pose potential health risk. Quantum dots have been successfully used in biological research due to the high photoluminescence and high resistance to photobleaching. To analyze SY efficiently, quantum dot-linked immunosorbent assay (QLISA) and enzyme-linked immunosorbent assay (ic-ELISA) were developed on the basis of generated monoclonal antibody. A carboxyl group was introduced to SY and coupled with carrier proteins to synthesize artificial antigen. Under the optimal conditions, inhibitory concentrations (IC50 ) of SY were 1.9 ng/mL (ic-ELISA) and 3.4 ng/mL (QLISA); the limits of detection (LODs) were 0.2 ng/mL (ic-ELISA) and 1.0 ng/mL (QLISA), respectively. Cross-reactivities of the mAb toward eight kinds of analogues were<0.01%. The recovery rates in spiked foods and beverages were 75.6%∼120.1% (ic-ELISA) and 74.0%∼114.1% (QLISA), respectively.